“He didn’t say that thalassaemia might come up” — β-thalassaemia carriers’ experiences and attitudes - Cousens, Nicole E. (Springer-Verlag, 2013)
Tests for haemoglobinopathy carrier status are the commonest genetic screening tests undertaken internationally. Carrier screening for β-thalassaemia is not coordinated in Victoria, Australia, and is instead incorporated into routine practice where most women are screened antenatally, through a full blood examination (FBE). Little is known about how women are screened for β-thalassaemia in Australia as well as their attitudes towards the screening process. This study was conducted to explore carriers’ and carrier couples’ experiences of and attitudes towards β-thalassaemia screening in Australia. Semi-structured interviews with 26 recently pregnant female carriers and ten carrier couples of β-thalassaemia were carried out. Interviews were analysed using inductive content analysis. Unexpectedly, more than half of the women had been made aware of their carrier status prior to pregnancy, with FBEs carried out for numerous reasons other than thalassaemia screening. Most women did not recall being told about thalassaemia before notification of their carrier status and therefore did not make a decision about being screened. They were generally accepting for doctors to decide about testing; however, would have preferred to have been made aware of the screening test. Women also reported receiving insufficient information after being notified of their carrier status, leading to misconceptions and confusion. This genetic screening process, incorporated into routine care whereby informed decisions were not being made by patients, was apparently acceptable overall. Based on the results of this study, we make the following recommendations: (1) individuals should be made aware that they are being tested for thalassaemia at least before a specific thalassaemia diagnostic test is performed; (2) current understanding by known carriers of thalassaemia should be assessed and any misconceptions corrected; (3) written information should be provided to carriers; (4) referral of carrier couples to specialists in thalassaemia and genetics is strongly recommended; (5) the term ‘carrier of β-thalassaemia’ should be used rather than ‘thalassaemia minor’. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12687-012-0136-7) contains supplementary material, which is available to authorized users.